Microstructure, physicochemical properties, and adsorption capacity of deoiled red raspberry pomace and its total dietary fiber. (January 2022) - Li, Meixuan; Liu, Yixiao; Yang, Guang; Sun, Lanying; Song, Xingshun; Chen, Qihe; Bao, Yihong; Luo, Ting; Wang, Jinling
Abstract: The microstructure, physicochemical properties and adsorption capacities of deoiled red raspberry pomace (DRP) and its total dietary fiber (DRPF) were investigated in the study, aiming to evaluate their potential to use as functional food ingredients. The chemical composition showed that both DRP and DRPF were mainly made of lignin. Compared to DRP, DRPF exhibited significantly decreased total contents of sugar, fat, and crude protein, from 13.37%, 5.07% and 2.58% to 1.54%, 1.17% and 1.37%, respectively. The thermal gravity analysis revealed that DRP and DRPF were stable under 162 ° C and 197 ° C, respectively. DRPF showed higher water-holding capacity (8.97 g/g vs. 2.62 g/g in DRP), swelling ability (10.18 mL/g vs. 6.93 g/g in DRP) and water solubility (0.25% vs. 0.07% in DRP). DRP had significantly higher in vitro cholesterol, and glucose adsorption capacities. However, better adsorption capacity of toxic ions was shown in DRPF. Based on chemical composition and characteristics, DRP and DRPF are both ideal supplements for dietary fiber and might be suitable to use as anti-obesity ingredients. Moreover, DRPF may be a better choice for toxic ions removing food. Highlights: DRPF is dietary fiber extracted enzymically from DRP. DRP and DRPF was simultaneously studied for the first time. DRP had lower water-holding capacity, swelling ability and solubility. DRP had superior cholesterol, glucose, nitrite ions adsorption capacity in vitro. DRPF had advantages of higher toxic ions adsorption capacity.